House of whispers. 2, Ananse - Hopkinson, Nalo; Gaiman, Neil (Sandman Universe, 2020)
"The souls trapped in the Dreaming are restless, seeking any help they can attain to escape from their "predeceased" state. Erzulie calls upon the spider-god of stories, Anansi, to assist her in unraveling the truth behind her own history. But can Anansi be trusted with any truths he finds?"--Amazon.